2019
DOI: 10.1038/s41396-019-0447-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a thermophilic sulfur- and iron-reducing thaumarchaeote from a terrestrial acidic hot spring

Abstract: A deep-branching clade of Thaumarchaeota, conventionally called Terrestrial hot spring creanarchaeotic group (THSCG), is a missing link between thaumarchaeotic ammonia oxidizers and the deeper-branching non-ammonia oxidizers, such as Crenarchaeota and Candidatus Korarchaeota. Here, we report isolation of the first cultivated representative from the THSCG, named as NAS-02. Physiological characterization demonstrated that the isolate was a thermoacidophilic, sulfurand iron-reducing organoheterotroph, which was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…As consistent with our previous report [22], we confirmed that NAS-02 T was affiliated in THSCG that was located at the basal point of the phylum Thaumarchaeota in the phylogenetic tree of 16S rRNA genes ( Fig. 1a) and in the phylogenomic tree based on 122 archaeal marker proteins (Fig.…”
supporting
confidence: 92%
“…As consistent with our previous report [22], we confirmed that NAS-02 T was affiliated in THSCG that was located at the basal point of the phylum Thaumarchaeota in the phylogenetic tree of 16S rRNA genes ( Fig. 1a) and in the phylogenomic tree based on 122 archaeal marker proteins (Fig.…”
supporting
confidence: 92%
“…Members of non-AOA can grow in both anaerobic and aerobic conditions, and oxygen may influence the diversity and structure of non-AOA community ( Biggs-Weber et al, 2020 ). Since only few genomes and enrichment cultures for non-AOA Thaumarchaeota are available ( Kato et al, 2019 ), most of their metabolic potentials remain underexplored. Hence, more detailed studies are needed to comprehensively describe their physiology.…”
Section: Aoa In Estuariesmentioning
confidence: 99%
“…While a substantial number of ecological studies and several cultures and enrichments confirm the ammonia-oxidising activity of Thaumarchaeota, there is also evidence that ammonia oxidation is not universal in this phylum 9 13 . In particular, there is evidence that the early-diverging lineages of Thaumarchaeota (including the Group 1.1c, Group 1.3 and pSL12 lineages) do not require ammonia oxidation for growth 10 , 13 , and the ammonia oxidation machinery may have been acquired subsequently to the origin of Thaumarchaeota during, or after, the Great Oxygenation Event 2300 My ago 12 . While oxygen and pH have been recognised as driving forces of massive diversification through their evolutionary history 12 , 14 , the evolutionary mechanisms leading to such high phylogenetic and metabolic diversity have received little attention.…”
Section: Introductionmentioning
confidence: 99%